Minerals In The World Economy - Charles L. Kimbell (The National Institute for Occupational Safety and Health (NIOSH), 1981)
The year 1977 generally was a year of growth in overall world mineral industry activity, although there were downturns in major elements of the world's iron and steel industries. The sharp upturns in market economy nation activities that were noted in 1976, following the reduced performance levels of 1975, were moderated, and in the centrally planned economy nations, overall mineral industry activity apparently continued to increase, but at a pace in keeping with that of 1916 rather than at the higher rates of the earlier 1976's. Noteworthy during the year, if only in a negative sense, was the inability of world powers to reach any significant agreement on issues relating to deep seabed mining. Interest from a commercial viewpoint centered around deposits or so-called manganese nodules. These materials, which indeed are chiefly manganese in terms of their content on a quantitative basis, really were of commercial interest primarily far their copper, nickel, and cobalt content. Participants at the Third United Nations Law of the Sea Conference looked into seabed mining rights, but reached no mutually agreeable decisions.